Medication pattern and adherence to type II diabetes treatment at university hospital of Central India - Shamkuwar, Chetna A.; Meshram, Sushant H.; Kumari, Nalini (International Journal of Research in Medical Sciences, 2023)
Background: The estimated number of diabetics in India was 62.4 million in 2011 projected to rise 101.2 million by 2030. Rational medication pattern and adherence to treatment are key components of diabetes control. Study purpose is to evaluate medication pattern and assess adherence to treatment. Methods: Prospective, observational and questionnaire-based study. Medication pattern evaluated from prescriptions and adherence assessed with Morisky medication adherence scale. Result: Total 200 prescriptions were studied. 98 (49%) and 102 (51%) were male and female respectively. Majority were above 60 years of age. Co-morbid conditions were found in 175 (87%) patients with hypertension (72%), being more common. Patients were prescribed 1216 medications. The average number of drugs per prescription was 6.20. Oral hypoglycemic drugs were 22.69%. Commonly prescribed drugs were anti-hypertensive (15.70%), drugs for coronary artery disease (10.36%), antibiotics, NSAID, PPI, vitamins and minerals (31.99%). High, medium and low adherence were observed in 47%, 38% and 15% of patients. Males (61%) adherence more than females in high adherence group. Conclusions: This study demonstrates the variability of drug utilization in diabetics. More than fifty percent patient have medium and low adherence which affects control of diabetes. Factors leading to poor adherence should be studied for better control of diabetes.